Cellulose supported transition metal (Cu, Pd) catalysts for carbon-carbon and carbon-nitrogen bonds formation reactions - Islam, Md. Shaharul (2018)
This research mainly deals with the synthesis, characterization, and applications of functionalized cellulose supported heterogeneous metal catalysts for various types of cross-coupling reactions. Cross-coupling reactions generally proceed in the presence of homogeneous metal complexes. The practical limits to perform homogeneous catalysis reactions are complicated due to the difficulty in the separation of the product from the reaction mixture, as well as the inability to reuse the metal catalysts. To overcome these problems, scientific communities have investigated the use of various heterogeneous solid supports for metal catalyst species such as carbon nanotubes, graphene, silicates, polymers, metal oxides, and various hybrid inorganic materials. Although many economic and sustainable protocols have been employed by researchers dedicated to the development of green processes for cross-coupling reactions, there is still a high demand to explore more efficient catalysts for chemical transformation reactions. Nowadays, science and technology are shifting towards environmentally friendly, sustainable resources, and processes to investigate low-cost production of fine chemicals. In this perspective, natural biopolymers (cellulose) could be considered as acceptable solid support materials because of their promising merits such as being largely abundant in nature, having low density, bio-renewability, universal availability, low-cost and interesting chemical and mechanical properties. Therefore, natural cellulose would be a perfect solid support for catalysts. In this study, corn-cob cellulose was isolated from bio-waste corn-cobs, and the backbone of the cellulose was chemically modified through polymerization. The resulting polymeric functional group was converted into suitable poly(amidoxime) chelating ligand. The cellulose-supported poly(amidoxime) readily underwent a complexation reaction by treatment with metal (Pd/Cu) salts to give the corresponding cellulose-supported heterogeneous poly(amidoxime) metal complexes. The cellulose-supported palladium complex exhibited a high catalytic activity (0.1 to 0.05 mol%) towards Mizoroki-Heck cross-coupling reactions of aryl halides with a variety of olefins to give the corresponding coupling products of up to 97% yield. The electron withdrawing aryl halides processes higher yields compare to electron donating aryl halides. The palladium complex was also applied to the synthesis of Ozagrel, a thromboxane A2-synthetase inhibitor through Mizoroki-Heck reaction with 88% yield. The cellulose-supported poly(amidoxime) copper complex was applied to the Click reaction [Cu(II) 1 to 0.05 mol%] of organic azide with terminal alkyne to afford triazole in up to 96% yield. Moreover, copper nanoparticles were prepared from the copper complex and well stabilized by the poly(amidoxime) ligands. The copper nanoparticles were efficiently promoted the chemoselective Aza-Michael reaction [Cu(0) 0.1 to 0.005 mol%] of aliphatic amines with α, β -unsaturated compounds to give addition products in up to 95% yield. Additionally, all polymeric cellulose supported catalysts were easy to recover from the reaction mixture and reused several times without significant loss of their catalytic activities.